Sweated Industries, 1897 (1897)
1897 "Sweated Industries, 1897" [T0509b.jpg], 1897 These notes are from an investigation into low wages and long hours in the artificial flower-making trade in London. Many of those interviewed were home workers. The investigation was undertaken by the Christian Social Union (CSU) for a report to Her Majesty's Inspector of Factories and Workshops.